Improving the internal quantum efficiency of QD/QW hybrid structures by increasing the GaN barrier thickness. Issue 68 (12th November 2020) - Jia, Zhigang; Hao, Xiaodong; Lu, Taiping; Dong, Hailiang; Jia, Zhiwei; Ma, Shufang; Liang, Jian; Jia, Wei; Xu, Bingshe
Abstract : High-density V-shaped pits cause that InGaN/GaN multi-quantum well becomes QD/QW hybrid structure, and the internal quantum efficiency of the hybrid structure is improved by increasing the thickness of GaN barrier. Abstract : Three InGaN/GaN quantum well (QW) samples with different barrier thickness (Sample A: 15 nm, Sample B: 17.5 nm, and Sample C: 20 nm) were grown via a metal organic chemical vapor deposition (MOCVD) system. The InGaN/GaN QWs became QD/QW hybrid structures due to the high density of V-shaped pits (VPs), which cut the InGaN wells into InGaN quantum dots (QDs) and indium-rich (In-rich) QDs stemming from the indium phase separation. By increasing the thickness of GaN barriers, the interactions between InGaN wells are weakened; thus, the strain accumulation is relieved and the strain relaxation degree decreases. Abnormally, the residual internal strain first increased due to least VPs in B and then decreased for C. Lower internal strain weakens the strain-induced piezoelectric polarization effect and as a result, a higher electron–hole wave function overlap and radiative recombination efficiency are improved. Similarly, lower strain relaxation results in more homogeneous indium distribution, and accordingly, a slightly weaker carrier localization effect (CLE). The CLEs of the three samples are strong enough that carriers can be confined by localized states even at room temperature; thus, the slightly weaker CLE does not influence the internal quantum efficiency (IQE). More importantly, InGaN QDs or QWs with lower strain relaxation contain fewer stacking faults that can act as non-radiative recombination centers (NRRCs), improving the IQE. By analyzing the effects of strain-induced piezoelectric polarization, NRRCs and carrier localization on the IQE, it is found that less NRRCs are a major factor in improving the IQE of these QD/QW hybrid structures.